Financing tools based on urban land for better planning management - Barrantes-Chaves, Karla (2025)
The tools based on value capture allow governments to fund public infrastructure with part of the increase in the land value from properties that benefit from state investments. This paper presents a series of international case studies about public infrastructure financing tools based on value capture. The cases include cities in Asia, North America, Europe, Oceania, and Latin America. After analyzing these examples, an overview of the possibilities for using these tools in Costa Rica is obtained. The methodology used for this work involves a literature review in peer-reviewed databases using Boolean operators with previously established selection criteria. The search is then expanded with institutional documentation. This paper concludes with a reflection on the challenges and lessons learned in using such tools for financing public infrastructure and their potential application in the Costa Rican context.